Multicentric Giant Cell Tumor of Bone: Synchronous and Metachronous Presentation - Reiner Wirbel; Frank Blümler; Dirk Lommel; Guido Syré; Veit Krenn (Case Reports in Orthopedics)
A 27-year-old man treated 2.5 years ago for synchronous multicentric giant cell tumor of bone located at the right proximal humerus and the right 5th finger presented now with complaints of pain in his right hip and wrist of two-month duration. Radiology and magnetic resonance revealed multicentric giant cell tumor lesions of the right proximal femur, the left ileum, the right distal radius, and the left distal tibia. The patient has an eighteen-year history of a healed osteosarcoma of the right tibia that was treated with chemotherapy, resection, and allograft reconstruction. A literature review establishes this as the first reported case of a patient with synchronous and metachronous multicentric giant cell tumor who also has a history of osteosarcoma.